a)
\frac{1}{2} \\log_{16}(4x+3)>log_{16}(-4)\\4x+3>-4\\x>-\frac{7}{4}" alt="log_{16}(4x+3)>\frac{1}{2} \\log_{16}(4x+3)>log_{16}(-4)\\4x+3>-4\\x>-\frac{7}{4}" align="absmiddle" class="latex-formula">
б) ![log_{\frac{1}{4}}(4x+3)\geq - 1\\log_{\frac{1}{4}}(4x+3)\geq log_{\frac{1}{4}}4\\4x+3\geq 4\\x\geq \frac{1}{4} log_{\frac{1}{4}}(4x+3)\geq - 1\\log_{\frac{1}{4}}(4x+3)\geq log_{\frac{1}{4}}4\\4x+3\geq 4\\x\geq \frac{1}{4}](https://tex.z-dn.net/?f=log_%7B%5Cfrac%7B1%7D%7B4%7D%7D%284x%2B3%29%5Cgeq%20-%201%5C%5Clog_%7B%5Cfrac%7B1%7D%7B4%7D%7D%284x%2B3%29%5Cgeq%20log_%7B%5Cfrac%7B1%7D%7B4%7D%7D4%5C%5C4x%2B3%5Cgeq%204%5C%5Cx%5Cgeq%20%5Cfrac%7B1%7D%7B4%7D)
в)![log^{2}_{4}x-log_{4}x-6<0\\(log_{4}x-3)(log_{4}x+2)<0\\ log^{2}_{4}x-log_{4}x-6<0\\(log_{4}x-3)(log_{4}x+2)<0\\](https://tex.z-dn.net/?f=log%5E%7B2%7D_%7B4%7Dx-log_%7B4%7Dx-6%3C0%5C%5C%28log_%7B4%7Dx-3%29%28log_%7B4%7Dx%2B2%29%3C0%5C%5C)
0}} \right.\\\left \{ {{log_{4}x<3} \atop {log_{4}x>-2}} \right. \\\left \{ {{log_{4}xlog_{4}\frac{1}{16} }} \right. \\\left \{ {{x<64} \atop {x>\frac{1}{16} }} \right. \\(1/16 ; 64)" alt="\left \{ {{log_{4}x-3<0} \atop {log_{4}x+2>0}} \right.\\\left \{ {{log_{4}x<3} \atop {log_{4}x>-2}} \right. \\\left \{ {{log_{4}xlog_{4}\frac{1}{16} }} \right. \\\left \{ {{x<64} \atop {x>\frac{1}{16} }} \right. \\(1/16 ; 64)" align="absmiddle" class="latex-formula">
г)
log_{2}(2-7x)\\3x-1>2-7x\\10x>3\\x>\frac{3}{10}" alt="log_{2}(3x-1)>log_{2}(2-7x)\\3x-1>2-7x\\10x>3\\x>\frac{3}{10}" align="absmiddle" class="latex-formula">